PELATIHAN LITERASI DIGITAL BAGI GURU SD N 1 TOYAREKA GUNA MENDUKUNG PEMBELAJARAN KURIKULUM MERDEKA - Mustofa, Dinar; Darmayanti, Irma; Pramono, Agus; Saputra, Dhanar Intan Surya; Kusuma, Velizha Sandy; Apitiadi, Satyo Dwi (LPPM Universitas Nusa Mandiri, 2025)
This community service project aims to enhance the digital literacy of teachers at SD Negeri 1 Toyareka in supporting the implementation of the Merdeka Curriculum. One of the challenges teachers face is their limited ability to utilize digital technology and artificial intelligence (AI) to create interactive and relevant learning experiences for students. The program was conducted through socialization, digital literacy training, AI technology introduction, and continuous mentoring and evaluation. During the training, teachers were provided with insights into digital platforms that can be used in the teaching and learning process, as well as AI applications to assist in student data analysis and the creation of adaptive learning materials. The training results show a significant improvement in teachers' skills in using digital technology and AI, particularly in creating more personalized and compelling learning experiences. Teachers could utilize digital tools to manage their classrooms more efficiently and use AI to personalize learning based on students' needs. The program evaluation revealed that teachers felt more confident using technology to support teaching and learning. The sustainability of this program is ensured through regular mentoring and assessment, as well as plans for further training to keep teachers updated with rapidly evolving technologies. This initiative is expected to be a model for developing digital literacy in other schools.